Evolution of Anticariogenic Resin‐Modified Glass Ionomer Cements. Issue 4 (20th April 2021) - Malik, Zuleikha; Qasim Butt, Danial; Qasim Butt, Zainab; Muhammad, Nawshad; Kaleem, Muhammad; Liaqat, Saad; Adnan Khan, Muhammad; Samad Khan, Abdul
Abstract: With advancing technology and exponential growth in scientific research, new perspectives in dental materials are being discovered. Conservative dentistry advocates maximum tooth preservation by revised restorative materials. Resin‐modified glass ionomer cement (RMGIC) is a flexible group of dental materials that can be used for restoring, lining, luting, and sealing teeth. Much advancements have been achieved to make them inherently anticariogenic as an adjunct to their fluoride release. In an attempt to resolve issues of secondary caries, white spot lesions, and cavitation, nanoparticles of metals such as zinc, silver, and titanium have been added. Biomaterials with regenerative potential like bioactive glass and hydroxyapatite are being explored as well. Similarly, antibiotics and natural resins like propolis and chlorhexidine have shown tremendous response against caries causing the oral pathogen Streptococcus mutans . This comprehensive review sheds light on the recent research in RMGIC, contemplating the repercussions of incorporating antibacterial agents into these types of cement. Abstract : Resin‐modified glass ionomer cements is a flexible group of dental materials that can be used for restoring, lining, luting, and sealing teeth. This review describes possible antimicrobial agents such as nanoparticles, drugs, or other functionalized materials which have been incorporated in resin‐modified glass ionomer cements for preventing bacterial growth, biofilm formation, and white lesions.